Studi tentang Kepemimpinan Spritual dan Organizational Citizenship Behavior : Peran Otonomi sebagai Intervening - Tamri Tamri; Rudi Erwandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to examine the relationship between spiritual leadership, autonomy, and Organizational Citizenship Behaviors (OCB). OCB is divided into two types, including altruism, organizational citizenship behaviors toward an individual (i.e., behaviors that are directly helpful to a specific individual and indirectly contribute to the organization) and conscientiousness, organizational citizenship behaviors toward an organization or a team (i.e., behaviors that directly contribute to the organization). A quantitative survey was performed on a sample of public services (N = 282) from Lubuklinggau City to study the influence of spiritual leadership on OCB, especially altruism and conscientiousness. The data analyzed by using PLS (Partial Least Square) program results indicate that spiritual leadership strongly predicted autonomy mediated spiritual leadership's effect on both altruism and conscientiousness. Keywords: spiritual leadership, autonomy altruism and conscientiousness